2014
DOI: 10.1111/pce.12370
|View full text |Cite
|
Sign up to set email alerts
|

The Medicago truncatula hypermycorrhizal B9 mutant displays an altered response to phosphate and is more susceptible to Aphanomyces euteiches

Abstract: Inorganic phosphate (Pi) plays a key role in the development of arbuscular mycorrhizal (AM) symbiosis, which is favoured when Pi is limiting in the environment. We have characterized the Medicago truncatula hypermycorrhizal B9 mutant for its response to limiting (P/10) and replete (P2) Pi. On P2, mycorrhization was significantly higher in B9 plants than in wild-type (WT). The B9 mutant displayed hallmarks of Pi-limited plants, including higher levels of anthocyanins and lower concentrations of Pi in shoots tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
(171 reference statements)
1
7
0
Order By: Relevance
“…truncatula (Truong et al, 2014) and Pisum sativum (Jones et al, 2015), where arbuscule proliferation appears analogous to what we have observed upon CO treatment. A few hypotheses can be made to explain this, each of which deserves further investigation.…”
Section: Exogenous Co Application Promotes Am Developmentsupporting
confidence: 87%
“…truncatula (Truong et al, 2014) and Pisum sativum (Jones et al, 2015), where arbuscule proliferation appears analogous to what we have observed upon CO treatment. A few hypotheses can be made to explain this, each of which deserves further investigation.…”
Section: Exogenous Co Application Promotes Am Developmentsupporting
confidence: 87%
“…As 40 cycles were performed for qPCR analysis, a gene was considered not to be expressed if DCt test gene -reference gene 26. Therefore, gene expression was quantified by the parameter 26 -DCt test gene -reference gene , which is higher when the test gene is more highly expressed (Bari et al, 2006;Truong et al, 2015). When normalizing AeCRN5 and AeCRN13 expression to AeTUB expression, as the average Ct of AeTUB was 28, the value 12 -DCt test gene -AeTUBgene was used for the quantification of gene expression.…”
Section: Rna Extraction Reverse Transcription and Quantitative Pcr Omentioning
confidence: 99%
“…To reduce the variation between experiments, the Medicago Genome Array of Affymetrix platform with 61278 probset IDs was selected. Some samples in four studies had these criteria (Table 1 , Figure 1 ) (Hogekamp et al, 2011 ; Bonneau et al, 2013 ; Truong et al, 2015 ; Floss et al, 2017 ). These samples were roots colonized with Gigaspora gigantean, Rhizophagus irregularis , or Glomus mosseae as well as non-inoculated ones.…”
Section: Resultsmentioning
confidence: 99%
“…In the original experiment (Truong et al, 2015 ), the impact of P limitation and both P and N limitation on Medicago truncatula A17 root transcriptome in response to Rhizophagus irregularis (previously known as Glomus intraradices ) were investigated. In the original experiment, the root transcriptome of both wild type plants and a hypermycorrhizal mutant (B9) grown on limiting or non-limiting phosphate were analyzed to determine which processes were in the hypermycorrhizal mutant.…”
Section: Methodsmentioning
confidence: 99%